2015
DOI: 10.15835/nsb739595
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Root and Stem Anatomy of Four Rare <i>Onobrychis</i> Mill. (Fabaceae) Taxa Endemic in Turkey

Abstract: Four endemic taxa of Onobrychis Mill. genus, some of them being classified in the endangered threat category, were investigated for root and stem anatomy. Onobrychis quadrijuga, O. argyrea subsp. argyrea, O. tournefortii and O. albiflora were studied in regard to specific anatomy for the first time within the hereby study. Anatomical characters as the size and shape of the periderm, cortex, cambium cells in root and epidermis, collenchyma, cortex, cambium and pith cells in stem belonging to these four Onobrych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A large number of bers was observed in the secondary phloem and xylem, especially in the innermost region, in all species analyzed, except in the secondary phloem at the stem base of S. polyphylla, which was visibly the region that presented fewer bers. The presence of sclerenchymatic brous cells, whether individual or in groups, is common in the cortex, secondary phloem, and secondary xylem in Fabaceae (Tekin and Yilmaz 2015). Silva et al 2013 found, in the stem of Erythrina velutina, groups of bers forming a band over the phloem, as seen in some of the four studied species The presence of lenticels was veri ed in A. niopoides and S. polyphylla at 18 months.…”
Section: Discussionmentioning
confidence: 78%
“…A large number of bers was observed in the secondary phloem and xylem, especially in the innermost region, in all species analyzed, except in the secondary phloem at the stem base of S. polyphylla, which was visibly the region that presented fewer bers. The presence of sclerenchymatic brous cells, whether individual or in groups, is common in the cortex, secondary phloem, and secondary xylem in Fabaceae (Tekin and Yilmaz 2015). Silva et al 2013 found, in the stem of Erythrina velutina, groups of bers forming a band over the phloem, as seen in some of the four studied species The presence of lenticels was veri ed in A. niopoides and S. polyphylla at 18 months.…”
Section: Discussionmentioning
confidence: 78%
“…The vascular cambium was clearly distinguish with as a region of 2-5 layers situated between the pith and cortex. Tekin and Yılmaz (2015) noted that in the cross section of the stems of four rare Onobrychis, the epidermis cell shapes were square, rectangular or rectangular oval, and that the cortex in these species was surrounded by parenhyma cells. Roots were ~1.3 mm in diameter with a uniform periderm (~11 µm) all around the root (Figure 8a,b).…”
Section: Vegetative Plant Parts Ultrastructurementioning
confidence: 99%
“…The protoxylem vessels were smaller than of the metaxylem vessels (Figure 8c). Tekin and Yılmaz (2015) documented that the stems and roots of Onobrychis sp. display a a similar composition.…”
Section: Vegetative Plant Parts Ultrastructurementioning
confidence: 99%